The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pon.4148
|View full text |Cite
|
Sign up to set email alerts
|

Examination of moderators of expressive writing in patients with renal cell carcinoma: the role of depression and social support

Abstract: Objective To identify groups most likely to benefit from an Expressive Writing (EW) intervention, we examined psychosocial variables as intervention moderators. We hypothesized that EW would be particularly effective for participants with high levels of depressive symptoms and social support at study entry. Methods Patients (n = 277; 60.6% male) with kidney cancer were randomly assigned to either an expressive (EW) or neutral writing (NW) condition. Intervention outcomes included measures of depressive sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…132 Secondary analyses from this study showed that the patients who benefited the most from the expressive writing intervention had both greater depressive symptoms and greater social support, as measured at baseline. 133 Interventions incorporating internet support groups have become popular, 134 with a Cochrane review including 6 studies with 492 women with breast cancer showing a small to moderate effect on depression, based on low-quality evidence. 135 None of the 6 studies included in the review assessed emotional distress specifically, and results from 2 studies showed no significant effect on anxiety when comparing the intervention and control groups.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…132 Secondary analyses from this study showed that the patients who benefited the most from the expressive writing intervention had both greater depressive symptoms and greater social support, as measured at baseline. 133 Interventions incorporating internet support groups have become popular, 134 with a Cochrane review including 6 studies with 492 women with breast cancer showing a small to moderate effect on depression, based on low-quality evidence. 135 None of the 6 studies included in the review assessed emotional distress specifically, and results from 2 studies showed no significant effect on anxiety when comparing the intervention and control groups.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…Increased social integration and interactions arising as a result of WED have been evidenced in studies outlining that participants assigned to experimental disclosure were more likely than controls to talk about their traumatic experience in the weeks or months following disclosure (e.g., Kovac and Range, 2000). However, it is important to note that expressive writing results in greater health benefits for individuals who perceive that social support is available (Milbury et al, 2017). As such, before athletes initiate WED, it may be prudent to identify and/or establish a supportive social network.…”
Section: Social Integrationmentioning
confidence: 99%
“…Four studies were conducted as RCTs [ 8 11 ]. Three interventions were group consultations [ 8 , 9 , 12 ], two were individual studies [ 13 , 14 ], two were couple therapy [ 10 , 11 ], two were technology based (via phone or online support) [ 12 , 15 ] and one was a relaxation training [ 16 ].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Social, relationship and/or familial wellbeing were also well distributed through the majority of the studies. Depression was assessed using different tools: Depressive Symptoms were assessed using the Center for Epidemiologic Studies Depression Scale (CES-D) in two studies [ 6 , 8 ], with the Hospital Anxiety and Depression Scale (HADS) in three studies [ 17 , 18 , 20 ] and using Patient Reported Outcomes Measurement Information System (PROMIS0 depression itembank CAT in one study [ 11 ] and self-administered Depression Anxiety Stress Scale (DASS-21) in one study [ 16 ].…”
Section: Evidence Synthesismentioning
confidence: 99%